Mineral Characterization Study of Gold Deposit in Tawau, Sabah Focusing on Mineralogy and Geochemistry - Maijin, Richell (Universiti Sains Malaysia, 2022)
Tawau gold mine is included in the low sulfidation epithermal gold deposit system. The gold deposit is within the Tawau Peninsular. The Tawau Peninsular is underlain by the Oligocene to Middle Miocene sediments of the Kalumpang formation that consist predominantly of mudstone and shale with inter-bedded sandstone, conglomerate, limestone, and rare chert. The research purpose is to analyze the mineralogy and geochemistry of gold vein deposits and determine the system of the ore deposits. The mineral characterization study is an important stage in the development and operation of mining and mineral processing systems. The minerals' chemical composition, size, morphology, and association are all factors influencing the attraction of the deposit or products produced from it, and therefore their success as a commercial venture. The method employed in this study is a combination of X-Ray Fluorescent (XRF), Micro X-ray Fluorescence (µXRF), Inductively Coupled Plasma-Mass Spectrometry (ICP-MS), Scanning Electron Microscopy (SEM) and X-Ray Diffractometry (XRD). The study of the sample revealed the presence of pyrite, chalcopyrite, bornite, sphalerite, galena, and quartz as the main gangue mineral. Gold is not observed as free gold and possibly occurs as a sub-micron scale or solid solution. Based on those characteristics of the mineralogy and geochemistry this study showed that low sulfidation epithermal gold ore deposit in this area is refractory ore with high base metals.